Alliance Network Centrality, Board Composition, and Corporate Social Performance - Macaulay, C.; Richard, O.; Peng, Mike; Hasenhuttl, M. (Springer Netherlands, 2017)
What critical characteristics do firms have that determine the scale and scope of corporate social responsibility activities they undertake? This paper examines two disparate predictors of corporate social performance. First, using the lens of the resource-based view, we examine the role of alliance network centrality on corporate social performance. We find that centrality enhances corporate social performance. Second, we investigate how board composition affects corporate social performance. Specifically, drawing on stakeholder theory, we find that the percentage of female directors predicts greater corporate social performance. In addition, we look at the influence of outside directors on this relationship. Our findings show that the presence of more outside directors positively moderates the relationship between female directors and corporate social performance.